DETERMINAN NILAI PERUSAHAAN - Tania Monica Mardji (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This study aims to examine the effect of Leverage, Profitability, Firm Size, and Intellectual Capital on Firm Value. The population in this study are companies listed on the Non-Primary Consumer Goods Sector of the Indonesia Stock Exchange for the period 2017-2021. The sample obtained was selected through purposive sampling technique of 136 companies, so that 14 samples of companies were obtained over a period of 5 years, so that 70 observations were obtained. The analytical techniques processed using the IBM SPSS Statistics 25 application are descriptive statistical analysis, data pooling test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that Leverage, Profitability, and Firm Size each had a positive and insignificant effect on Firm Value, while Profitability had a positive and significant effect on Firm Value.